The prospective evaluation and risk factors of dysphagia after surgery in patients with oral cancer - Hasegawa, Takumi (J Otolaryngol Head Neck Surg, 2021)
BACKGROUND: This prospective study investigated the change of swallowing ability using the Swallowing Ability Scale System (SASS) and swallowing-related quality of life (QOL) by Performance Status Scale for Head and Neck Cancer patients (PSS-H&N). This study also investigated the risk factors for postoperative dysphagia in patients who received reconstructive surgery for oral cancer. SUBJECTS AND METHODS: This study included 64 patients (33 men and 31 women) who underwent radical surgery with neck dissection and reconstructive surgery for oral cancers between July 2014 and February 2018. We evaluated risk factors for poor swallowing ability after treatment, including demographic factors, preoperative factors and perioperative factors, with univariate and multivariate analyses. The change of swallowing ability by the SASS and swallowing-related QOL by PSS-H&N were evaluated prospectively prior to the initiation of surgery within 1 week and at 1 and 3 months after treatment. RESULTS: Advanced T stage (T3, 4) (odds ratio (OR) = 79.71), bilateral neck dissection (OR = 20.66) and the resection of unilateral or bilateral suprahyoid muscles (OR = 17.00) were associated with poor swallowing ability after treatment. The scores for time for food intake and Eating in Public were associated with decrease of QOL in the poor group. CONCLUSIONS: We propose that clinicians consider the risk factors identified in this study and pay close attention to the management of oral cancer patients with reconstructive surgery. GRAPHICAL ABSTRACT: [Image: see text]